2020
DOI: 10.1097/opx.0000000000001555
|View full text |Cite
|
Sign up to set email alerts
|

Findings from Optometrists' Practices in Advising about Lifestyle Study

Abstract: SIGNIFICANCE Lifestyle influences eye health and other chronic diseases. All health care providers, not just primary care physicians, should have the necessary information and training to advise and refer patients on lifestyle to take advantage of opportunities to provide such advice. PURPOSE The extent to which optometrists offer lifestyle advice to their patients is largely unknown. The Optometrists' Practices in Advising about Lifestyle (OPAL) study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 23 publications
1
7
1
Order By: Relevance
“…In contrast to the previous studies described above, this study found that 74% provided advice about smoking, 81% about the importance of a healthy diet and 79% regarding dietary supplements. The number of optometrists discussing smoking with patients with AMD was substantially higher in this study compared to others, but the percentage of practitioners offering dietary supplement advice was lower than previously reported [ 57 ]. However, the sample in this study was smaller than the other studies despite participants being contacted 3 times to encourage a response.…”
Section: Resultscontrasting
confidence: 76%
See 4 more Smart Citations
“…In contrast to the previous studies described above, this study found that 74% provided advice about smoking, 81% about the importance of a healthy diet and 79% regarding dietary supplements. The number of optometrists discussing smoking with patients with AMD was substantially higher in this study compared to others, but the percentage of practitioners offering dietary supplement advice was lower than previously reported [ 57 ]. However, the sample in this study was smaller than the other studies despite participants being contacted 3 times to encourage a response.…”
Section: Resultscontrasting
confidence: 76%
“…In another study evaluating only optometrists, Sahli et al (2020) administered postal surveys to 42 optometrists to examine the lifestyle advice that optometrists offer, to whom such advice is offered and reasons for not offering advice [ 57 ]. In contrast to the previous studies described above, this study found that 74% provided advice about smoking, 81% about the importance of a healthy diet and 79% regarding dietary supplements.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations